2015
DOI: 10.1016/j.aoas.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of banana peels supplemented diet on acute liver failure rats

Abstract: Peel of vegetables and fruits are of the most important part that helps in protecting the body from diseases, getting rid of the free radicals, as they contain vitamins and minerals which are antioxidant, in addition to phenols. Previous studies have proved the existence of vitamin C, E, and B6 in banana peels, especially vitamin C that can act as an antioxidant.The present study was performed to examine the effect of fresh and dried banana peels consumption on liver function (albumin, GPT, GOT, LDH, GGT and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 31 publications
0
20
2
3
Order By: Relevance
“…Beberapa hasil penelitian melaporkan bahwa kulit pisang dapat dimanfaatkan hingga 3-20% dalam pakan broiler (Widjastuti & Hernawan, 2012;Koni, 2013;Farman et al, 2016), tetapi kadar serat kasar dan tanin yang tinggi menyebabkan terbatasnya pemanfaatan kulit pisang sebagai pakan monogastrik. Kadar serat kasar pada kulit pisang mencapai 18,01% (Widjastuti & Hernawan, 2012); 18.71% (Koni, 2013), 36,7% (Hudiansyah, Sunarti, & Sukamto, 2015); 44,28% (Mosa & Khalil, 2015) dan kadar tanin 4,87% (Hudiansyah et al, 2015).…”
Section: Pendahuluanunclassified
“…Beberapa hasil penelitian melaporkan bahwa kulit pisang dapat dimanfaatkan hingga 3-20% dalam pakan broiler (Widjastuti & Hernawan, 2012;Koni, 2013;Farman et al, 2016), tetapi kadar serat kasar dan tanin yang tinggi menyebabkan terbatasnya pemanfaatan kulit pisang sebagai pakan monogastrik. Kadar serat kasar pada kulit pisang mencapai 18,01% (Widjastuti & Hernawan, 2012); 18.71% (Koni, 2013), 36,7% (Hudiansyah, Sunarti, & Sukamto, 2015); 44,28% (Mosa & Khalil, 2015) dan kadar tanin 4,87% (Hudiansyah et al, 2015).…”
Section: Pendahuluanunclassified
“…What about if banana peels can potentially cause liver failure in rats, does the potential liver failure affect cows? 48 Is deadly harm to rats acceptable but deadly harm to cows unacceptable? Before a construction company can assess the financial, legal, and social risk of integrating waste banana peels as a renewable supply chain material, there should be a definition of when the use of waste banana peels does not create harm to the nutritional needs or physiological safety of individuals and species that are completely unrelated to and disconnected from the building material production or construction processes.…”
Section: Materials Passports Facilitate Normative Evaluations Of Agrimentioning
confidence: 99%
“…The resultant in the same table revealed that the rats fed on banana peels;mangopeels and mixture of them were reduction in the elevated serum activity of AST and ALT level compared with positive group. These results agreement with ( Khan et al, 2008, Saeed .,2015 and El -Tantawy ., 2015) who reported that, the activities of ALT and AST in serum were significantly increased in lead exposed rats (Mosa andKhalil, 2015, El Makawy et al , 2015)showed that banana peelsand mango peels have good protective effects against acute hepatic injury in rats. 8) also showed that increased in the concentration of uric acid, urea and creatinine in positive group (2.87, 147.92 and 0.98 mg/dl) than negative control group was 1.82, 97.21 and 0.57 mg/dl, respectively.Whereas, the rats fed banana peels,mango peels and combination of them were significant reduction and the best result group was fed on mixturebanana and mango peels.…”
Section: Body Weight Gaintotal Feed Intakeand Feed Efficiency Ratio Of Rats Suffering From Lead Toxicitymentioning
confidence: 99%